2004
DOI: 10.1002/gps.1115
|View full text |Cite
|
Sign up to set email alerts
|

Validation of short screening tests for depression and cognitive impairment in older medically ill inpatients

Abstract: The GDS4 and OMC appear to be useful instruments for screening for depression and cognitive impairment among older medical inpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 26 publications
3
31
1
Order By: Relevance
“…The Blessed test is a brief screening measure of cognitive impairment with demonstrated reliability [37] and validity when compared to the mini-mental status exam [40]. The measure is easily administered and discriminates between mild, moderate, and severely impaired patients [37].…”
Section: Blessed Test Of Orientation Memory and Concentrationmentioning
confidence: 99%
“…The Blessed test is a brief screening measure of cognitive impairment with demonstrated reliability [37] and validity when compared to the mini-mental status exam [40]. The measure is easily administered and discriminates between mild, moderate, and severely impaired patients [37].…”
Section: Blessed Test Of Orientation Memory and Concentrationmentioning
confidence: 99%
“…For example, for women with early stage breast cancer, the recommended cut-off scores resulted in under-reporting of psychiatric morbidity, compared with DSM-IV clinical diagnoses (Ramirez et al, 1995;Hall et al, 1999;Love et al, 2002). The shortened version of the Geriatric Depression Scale (GDS-15) (Sheik and Yesavage, 1986) has been validated with older adults (Lesher and Berryhill, 1994) as well patients with medical problems (Meara et al, 1999;Goring et al, 2004) and has provided estimates of the prevalence of depression in CHF in-patients (Jiang et al, 2001). Neither questionnaire has yet been validated in patients with CHF, despite the high reported prevalence rates of mood disorders in this population (Haworth et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Both the sensitivity and specificity of the 6-CIT in detecting the presence of cognitive impairment were ≥90%. In a comparable UK-based study, a 6-CIT cut-off of 10/11 was found optimal in detecting cognitive impairment in a sample of 153 acute hospital inpatients [12]. This study similarly used a standardised MMSE cut-off score of ≤23 as the reference standard for cognitive impairment and found a sensitivity of 85.6% and a specificity of 86.8% for the 6-CIT.…”
Section: Review Of 6-cit Usementioning
confidence: 95%
“…It is scored out of 28; higher scores indicate greater impairment. It has been utilised in a broad range of settings, including screening for dementia in primary care [11], cognitive screening in acute care [12], in large population-based studies [13] and in studies of Alzheimer's disease [14,15]. It has been used as a reference standard in evaluating other cognitive tools/assessments [16,17] and recommended as a cognitive screening tool in hospitals [18].…”
Section: Introductionmentioning
confidence: 99%